Earnings Management in View of Information Asymmetry, Audit Tenure and Company Size: An Empirical Study - Chindy Faradhifa; Asih Handayani (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2024)
This study aimed to determine and analysis the effect of information asymmetry, audit tenure, and company size on earnings management in consumer non-cyclicals companies for the period 2018-2022. The research method used was descriptive associative with a quantitative approach. The type of data used was secondary data with a population of 87 companies. The sample selection technique used purposive sampling, and 15 companies were selected with a total of 75 data points. Data analysis involved descriptive test analysis, classical hypothesis testing (including normality, multicollinearity, heteroscedasticity, and autocorrelation tests), multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing (partial and simultaneous tests). Data processing was conducted using eviews version 12 software with a confidence level of 5%. This study’s novelty lay in its research object and period, as previous studies had focused on manufacturing companies in 2022. The results indicated that information asymmetry and audit tenure did not affect earnings management, while company size did. Large companies tended to have higher opportunities for earnings management than small companies due to their resource utilization. Abstrak - Penelitian ini bertujuan untuk mengetahui dan menganalisis asimetri informasi, audit tenure dan ukuran perusahaan terhadap manajemen laba pada perusahaan consumer non-cyclicals periode 2018-2022. Metode penelitian yang digunakan adalah deskriptif asosiatif dengan pendekatan kuantitatif. Jenis data yang digunakan adalah data sekunder dengan populasi sebanyak 87 perusahaan. Teknik pemilihan sampel menggunakan teknik purposive sampling dan sampel yang terpilih adalah 15 perusahaan dengan total data observasi sebanyak 75 data. Analisis data menggunakan analisis uji deskriptif, pengujian hipotesis klasik meliputi uji normalitas, uji multikolinearitas, uji heteroskedastisitas dan uji autokorelasi, analisis regresi linier berganda, analisis koefisien determinasi, pengujian hipotesis meliputi uji parsial (uji t) dan uji simultan (uji f). Pengolahan data menggunakan bantuan software eviews versi 12 dan tingkat kepercayaan yang digunakan adalah 5%. Novelty pada penelitian ini adalah objek dan periode penelitian, dimana sebelumnya menggunakan objek penelitian perusahaan manufaktur tahun 2022. Berdasarkan hasil penelitian diketahui bahwa asimetri informasi dan audit tenure tidak berpengaruh terhadap manajemen laba, sedangkan ukuran perusahaan berpengaruh terhadap manajemen laba. Perusahaan besar cenderung memiliki kesempatan melakukan manjemen laba lebih tinggi dibandingkan perusahaan kecil dengan memanfaatkan sumber daya yang dimilikinya.